Rancang Bangun Prototipe Insinerator Pemusnah Sampah Tanpa Bahan Bakar pada Tempat Pengolahan Sampah Desa Karang Mukti - Kasda; Yusup Yulianto; Kafi Mufti; Rifki Ruman Nulhakim (Universitas Proklamasi 45, 2026)
This research was conducted as an effort to overcome the problem of domestic waste in Karang Mukti Village, Cipeundeuy Subang. This is to realize community self-sufficiency at the village level in managing waste independently in a better and more efficient way. The initial step, this research focuses on the design and manufacture of a prototype of a waste burner (Incinerator) that can be operated without using fuel (self-burning) and the combustion chamber suhue is designed to reach more than 800oC. With the self-burning system in this incinerator design, it is expected to save operational costs because it will be operated in the village level area. The combustion system utilizes the heat from burning the waste itself (self-burning) with a combustion chamber design lined with heat-resistant walls from materials with good insulating properties, namely refractory bricks. The air flow entering the combustion chamber is generated from natural draft by determining the diameter and height of the chimney. Based on the design results, the Incinerator has a height of 2,000 mm, a length of 1,200 mm and a width of 1,200 mm. The chimney has a diameter of 200 mm and a height of 6,000 mm. Based on the results of domestic waste combustion tests, the lowest suhue in the combustion chamber was 306oC and the highest was 1,100oC. The lowest combustion capacity was 60 kg/hour and the highest was 255 kg/hour. Suhue fluctuations in the combustion chamber and combustion capacity are greatly influenced by the mixture conditions and humidity of the domestic waste fed into the combustion chamber.